Peripheral Intravenous Catheter related Thrombophlebitis- Incidence and Risk Factors A Cross Sectional Study - Zohaib Jamal, Zohaib Jamal; Muhammad Umair, Muhammad Umair; Rabi Zubair, Rabi Zubair; Nowera Zafar, Nowera Zafar; Fatima Rauf, Fatima Rauf; Muhammad Affif, Muhammad Affif (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Introduction: Peripheral Intravenous Cannulation is indispensable in modern day clinical practice. Thrombophlebitis is a very common and consequential problem related to peripheral intravenous catheterization. Methods: This descriptive cross sectional study was conducted in Allied Hospitals of Rawalpindi Medical University in three months on 170 patients. All the patients with peripheral venous catheter inserted for 72 hours were enrolled and those having skin rash or allergy to any medication or discharged from hospital or cannula removed before 72 hours were excluded from the study. The data was collected by using a predesigned pro forma, the variables included were age, gender, specific specialty, catheter insertion site, catheter gauge, underlying diseases such as diabetes mellitus, hypertension, hyperlipidemia and renal failure and smoking. Thrombophlebitis was graded using Visual Infusion Phlebitis Score suggested by Infusion Nurses Society. The data was entered and analysed using SPSS version 23 and Chi Square test was applied to check statistical significance. Results: The incidence of thrombophlebitis found in this study was 53.5%. The most common grade found was Grade 2 (52.7%) followed by Grade 1 (35.1%) and 3(12.1%). Increased incidence of thrombophlebitis in this study was found in younger age group (16-40years), females admitted in medical units, large sized catheters inserted on hands, hypertensive and hyperlipidemic patients and significant associations were Diabetes Mellitus (P=0.004), Smoking (P=0.004) and Catheterization without Gloves(P= 0.003). Conclusion: Peripheral intravenous catheterization is still on going and is a very significant problem in Allied Hospitals of Rawalpindi Medical University. Future studies should be made to improve the understanding of risk factors for thrombophlebitis especially comorbidities like Diabetes Mellitus and to discover more effective preventive methods. Key words: Intravenous cannula, Thrombophlebitis, Visual Infusion Phlebitis Score